2022 Fifth International Workshop on Mobile Terahertz Systems (IWMTS) 2022
DOI: 10.1109/iwmts54901.2022.9832441
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Structure Simulation Study of In0.53Ga0.47As/AlAs Double-Barrier Resonant Tunnelling Diodes

Abstract: In this paper, we report about an epitaxial structure simulation study of In0.53Ga0.47As/AlAs double-barrier resonant tunneling diodes (RTD) employing Atlas TCAD quantum transport simulation software developed by SILVACO Inc., which is based on the non-equilibrium Green's function formalism. We analyse how epitaxial layers design impacts the heterostructure static current density-voltage characteristic, including barriers, quantum well (QW), and lightly-doped spacer layers, as well as the employment of a high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The proposed n-type intraband epitaxial structure consists of an indium gallium arsenide/aluminium arsenide (In 0.53 Ga 0.47 As/AlAs) double-barrier quantum well (DBQW) structure featuring moderately-thick AlAs barriers (≃ 1.46 nm) and In 0.53 Ga 0.47 As QW (≃ 4.39 nm), asymmetric spacers, and heavily-doped emitter/collector contacts (N D = 5 × 10 19 cm −3 ), grown on top and lattice-matched to a semi-insulating (SI) InP substrate, which was designed through a non-equilibrium Green's function (NEGF)-based quantum transport simulation tool [4] to achieve moderate peak current density J p ∼ 2 mA/µm 2 and large voltage swing ∆V > 1 V [5]. The heterostructure was then investigated through the microfabrication and characterisation of RTD devices.…”
Section: Rtd Heterostructurementioning
confidence: 99%
“…The proposed n-type intraband epitaxial structure consists of an indium gallium arsenide/aluminium arsenide (In 0.53 Ga 0.47 As/AlAs) double-barrier quantum well (DBQW) structure featuring moderately-thick AlAs barriers (≃ 1.46 nm) and In 0.53 Ga 0.47 As QW (≃ 4.39 nm), asymmetric spacers, and heavily-doped emitter/collector contacts (N D = 5 × 10 19 cm −3 ), grown on top and lattice-matched to a semi-insulating (SI) InP substrate, which was designed through a non-equilibrium Green's function (NEGF)-based quantum transport simulation tool [4] to achieve moderate peak current density J p ∼ 2 mA/µm 2 and large voltage swing ∆V > 1 V [5]. The heterostructure was then investigated through the microfabrication and characterisation of RTD devices.…”
Section: Rtd Heterostructurementioning
confidence: 99%
“…In this paper, we report about a lattice-matched to InP indium gallium arsenide/aluminium arsenide (In 0.53 Ga 0.47 As/AlAs) double-barrier RTD epitaxial structure with high-power performance in the low-terahertz range (∼ 100−300 GHz). Based on the simulation study we reported in [6], we designed and optimised the heterostructure for high-power operation. RTD devices were fabricated and characterised to extract the associated static current density-voltage JV characteristic and small-signal equivalent circuit parameters, from which the high-frequency RF power performance of the heterostructure was investigated.…”
Section: Introductionmentioning
confidence: 99%